Alcoholism and addiction, epidemiology and prevention - Avezova Guloyim Sattarovna (Genius Journals, 2023)
Alcoholism (Latin alcoholism’s), as well as drunkenness, chronic alcoholism, chronic alcohol intoxication, alcoholism, alcohol toxicomania, etc. is a chronic mental progressive disease, a type of toxicomania, addiction to alcohol (ethyl alcohol) and mental and physical dependence on it. characterized by being Alcoholism is characterized by loss of control over the amount of alcohol consumed, increased tolerance to alcohol (an increase in the amount of alcohol required to maintain satiety), abstinence syndrome, toxic organ damage, and some of the effects that occur during intoxication. characterized by inability to remember events
Keywords: Alcoholic beverages; medicine; digestive system